Rodent Animal Models for Surrogate Analysis of Cell Therapy in Acute Liver Failure - Christ, Bruno; Brückner, Sandra (Frontiers in Physiology, 2012)
Without therapeutic intervention acute liver failure is the consequence of a progredient destruction of the liver parenchyma due to metabolic exhaustion of the hepatocytes. Perivenous hepatocytes are responsible for the detoxification of noxes via the cytochrome P450 enzyme system. Liver transplantation is the only remaining therapeutic option in the end-stage of the disease. Assuming that metabolic capacity could be provided by healthy hepatocytes and thus substitute for the genuine parenchymal cells hepatocyte transplantation since quite some time is considered to be an alternative to whole liver transplantaton. While this hypothesis achieved proof-of-concept in animal trials clinical breakthrough is still awaiting success, the reasons of which are ongoing matter of debate. In recent times mesenchymal stem cells came into focus as a transplantable cell source to treat ALF. Interestingly, as demonstrated in various rodent animal models their mode of action is rather based on trophic support of hepatocytes remaining in the damaged host parenchyma rather than substitution of tissue loss. Mechanistically, either direct or indirect paracrine effects from the transplanted cells acting pro-proliferative, anti-apoptotic and anti-inflammatory seem to trigger the regenerative response of the residual healthy hepatocytes in the otherwise lethally injured liver parenchyma. Thus, allogeneic mesenchymal stem cells may be the best choice for the treatment of ALF taking advantage of their short-term benefit to sustain the critical phase of the acute insult avoiding long-term immunosuppression.